Efektivitas Tugas dan Tanggung Jawab Jurusita pada Pengadilan Agama Palu Kelas I A - Khair, Abdul; Malarangan, Hilal; Raden, Sahran (Lembaga Teewan Journal Solutions, 2026)
This study examines the effectiveness of the duties and responsibilities of court bailiffs (jurusita) at the Palu Class IA Religious Court. Using a qualitative approach with juridical-empirical methods, data were collected through interviews, observation, and documentation. The results show that jurusita at the Palu Religious Court carry out their duties in accordance with applicable procedural law, including conventional summons within the jurisdiction, summons for absent parties (ghaib), and electronic summons via the e-court system. Two legal requirements must be met for a summons to be valid: it must be official (resmi) and proper (patut). The barriers faced include limited human resources, geographic challenges, and inadequate information technology infrastructure. This study recommends strengthening jurusita capacity through training and policy improvement to support a simple, fast, and low-cost judicial process.